CONTEMPORARY ARTISTIC PRODUCTION AND REVOLUTIONARY PROCESSES IN TUNISIA - Gandolfi, Paola (European Scientific Journal, ESJ, 2014)
Focusing on contemporary artistic production and on the case of Tunisia, the article aims to understand how some change dynamics have partially been narrated by artistic creations during the years before Ben Ali’ s fall in 2011. Considering how the new media and the activism of the civil society have indirectly contributed for years to the change dynamics, being “underground” and “informal spaces” for learning social alternatives, the idea here is to observe how the artistic production has become sometimes a strategy of resistance and emancipation especially for the youth. A part of the artistic creations had already expanded, both at a visual and at an imaginative level ,the narrative spaces able to talk about alternatives, and to talk about ideas of freedom and dignity and social justice (afterwards at the core of the revolutionary processes). This interdisciplinary work, with a main anthropological approach, aims to understand how some artists, with their works, have gradually and semi-clandestinely contributed to narrate their daily life, to denounce the daily injustices and to spread an imaginary which has been at the core of the upraising. Among others, the lively and diversified underground youth or the alternative scene of young musicians, but also few artists internationally known, had expressed a dissent and a will for action that both deserve attention. Even now, in the actual delicate and difficult phase of transition, the artistic creations, especially the artistic movements of the youth, are exemplary contexts for understanding the degrees of maintenance of the public space and of actual practices of participation.